(untitled) (Research, Society and Development, 2022)
Providing children with chances to have a correct development is perhaps the most relevant for the human being. In the first years of life, a satisfactory development contributes to the formation of a human being with their developed potential, with a greater chance of becoming a safer subject, prepared to face the obstacles that life offers, thus reducing social and social inequalities. economics of our society. This is a scope review protocol on educational technology used to promote home care for children with delayed child development. The objective was to map the evidence in the literature on the topic addressed. The protocol defines the objectives, eligibility criteria, sources of evidence, graphing methods, results and conclusions related to the Scope Review questions and objectives. It was prepared based on the Preferred Reporting Items for Systematic Reviews and Meta Extension Scoping Rewiew and the Joana Brigs Institute Evidence Synthesis manual.